Developing variations: style and ideology in Western music - Subotnik, Rose Rosengard (Minneapolis University of Minnesota Press, 1991)
A collection of essays, most previously published on the critical theory, aesthetics, and social historiography of western classical music since the late 1700's. Based largely on the ideas of Theodor W. Adorno. A companion volume, Deconstructionist variations, is planned.